Ideation For Supportive Environment Using Conceptual Model For Knowledge Sharing Model - Hanafizan HUSSAIN (Communications of International Proceedings, 2021)
This study has been derived from the iterative process which reflect on the ideation on creating tools the supportive environment. The supportive environment offers people protection and foster participation in health and can be useful for well-being and good health. Therefore, this paper will elaborate the approach of using conceptual model for knowledge sharing model for the design process. Additionally, the design will be based on the supportive environment which is due to pandemic situation. Based on the observation of the current situation, the creation of the idea will be reflecting in the context of useful for age-friendly tool. This will spearhead towards the pre-serving behaviour when designing the interface in the design process.
Keywords: Conceptual Model for Knowledge Sharing Model; Behaviour; Interface Design Process; Age-friendly; Supportive Environment.